Enhancing Small-Medium IsLands resilience by securing the sustainability of Ecosystem Services: the SMILES Cost Action - Ioannis Vogiatzakis; Mario Balzan; Evangelia Drakou; Stelios Katsanevakis; Emilio Padoa-Schioppa; Elli Tzirkalli; Savvas Zotos; Xana Álvarez; Mart Külvik; Catarina Fonseca; Aristides Moustakas; Javier Martínez-López; et al. (Research Ideas and Outcomes, 2023)
European islands are hotspots of biological and cultural diversity, which, compared to mainland, are more vulnerable to climate change, tourism development, uncontrolled land-use changes and the consequences of financial crisis. These drivers of change have increasingly resulted in severe impacts on socio-economic and environmental parameters. Projected climate, land-use and socio-economic change will impact on islands’ biodiversity, ecosystem services and, in turn, on the quality of life of island inhabitants. Even if the existing methods can adequately predict the abovementioned changes of the larger islands, this is not the case for small and medium-size islands, where there is a need for refinement. Although ecosystem services (ES) assessments have been carried out worldwide in different geographical areas, islands are still under-represented. Despite the recognised islands’ importance and vulnerability, efforts to date have focused solely on the pressures they face. Still, we know little about ES supply, flow and demand and their spatio-temporal variability, whilst integrated approaches that consider ES cross-island realms (terrestrial, marine and their interface) remain scarce. Even more under-represented are studies that explore the telecoupled relationship amongst islands and their mainland counterparts. Moreover, the current conceptual approaches guiding ES mapping and assessment need further refinement to account for the complex manifestations of nature and culture arising from peoples’ interaction with island spaces. This paper discusses the creation of a platform for coordinated interdisciplinary research on several aspects of mapping and assessment of ES in small and medium European islands in order to synthesise and strengthen the knowledge base for conservation of island realms and contribute to their sustainable development.